Idiopathic Pulmonary Arterial Hypertension and Pulmonary Arterial Hypertension Associated With Congenital Heart Disease in Chinese Children: Similarities, Differences, and Prognostic Factors - Gu, Li; Li, Yuan Yuan; Gu, Ling; Xie, Liang; Liu, Han Min (Frontiers in Pediatrics, 2020)
Background: As the most common types of pulmonary arterial hypertension (PAH) in childhood, the similarities and differences in clinical characteristics and prognosis between idiopathic PAH (IPAH) and PAH associated with congenital heart disease (PAH-CHD) are not well-known. This study describes and compares clinical features of pediatric IPAH and PAH-CHD in a single center of China during an 11-year period and explores the prognostic factors. Methods: Twenty-five children with IPAH and 60 children with PAH-CHD, diagnosed in West China Second Hospital of Sichuan University from January 2008 to December 2018, were chosen as study objects. The follow-up deadline was June 2019, and the end-point was all-cause death. The baseline data, results of auxiliary examinations, treatment strategies, and follow-up outcomes were recorded and compared between IPAH and PAH-CHD patients to explore the similarities, differences, and prognostic factors. Results: The median diagnostic age for PAH-CHD patients was 2.3 years, which was younger than IPAH patients (7.3 years; p = 0.009). Sixty-eight percent of the IPAH patients presented with exercise-induced symptoms at initial diagnosis, whereas 58.3% of the PAH-CHD patients were asymptomatic (p < 0.001). Sixty percent of the IPAH patients were in World Health Organization-functional class (WHO-FC) III or IV, which was significantly worse than those of the PAH-CHD patients (p = 0.002). The incidence of ST-segment and T-wave (ST-T) change in children with IPAH (76.0%) was significantly higher than that (28.3%) in children with PAH-CHD (p < 0.001). Mean corpuscular volume (MCV), mean platelet volume (MPV), and platelet distribution width were larger in IPAH patients than those in PAH-CHD patients (p < 0.01). The 1-, 3-, and 5-year survival rates of IPAH and PAH-CHD patients were 53.5, 46.5, and 31.2% and 96.5, 93.1, and 77.6%, respectively (p < 0.05). WHO-FC III-IV [relative risk (RR) = 2.750, p = 0.008] and higher MPV (RR = 1.657, p = 0.006) predicted poor prognosis for pediatric PAH. Conclusion: We showed that there are more differences than similarities between IPAH and PAH-CHD patients in clinical characteristics. PAH-CHD patients have a better prognosis than IPAH patients. WHO-FC III-IV and higher MPV at initial diagnosis are independent risk factors for poor prognosis.